A Rare Cause of Ileus: Gallstone Ileus - Tunç, Emre; Ergün, Sefa; Şimşek, Osman; Pekmezci, Salih (Cerrahpaşa Medical Journal, 2021)
Gallstone ileus is a rare complication of cholelithiasis. It usually develops when stones in the gallbladder or biliary tract are fistulize into the gastrointestinal tract. Gallstone ileus is more common in women, and its incidence increases with age. The clinical symptoms and signs of gallstone ileus vary according to the place where the stone obstructs. Signs of intestinal obstruction such as nausea, vomiting,constipation, obstipation, aperistalsis, and abdominal distension are common. Contrast-enhanced computed tomography is the gold standard imaging method in the diagnosis. The treatment algorithm of gallstone ileus is controversial. In general, there are publications recommending simple enterotomy, one-stage surgery, and two-stage surgery. Patient’s age and comorbidities, fluid electrolyte imbalance, and segment of obstruction are considered for determining operative management. In our case, the diagnosis and treatment algorithm of the patient who applied to the Cerrahpaşa School of Medicine Emergency Clinic with ileus findings and was found to have gallstone ileus as a result of the examinations are presented. Nadir Bir İleus Sebebi: Safra Taşı İleusu Safra taşı ileusu kolelitiazisin nadir görülen bir komplikasyonudur. Safra kesesindeki ve safra yollarındaki taşların gastrointestinal sisteme fistülize olması ile gelişir. Safra taşı ileusu kadınlarda daha sık görülmekle birlikte, insidansı yaş ile birlikte artar. Hastalığın oluşturduğu semptomlar taşın obstrüksiyon oluşturduğu yere göre değişir. İntestinal obstrüksiyon bulguları olan bulantı, kusma, konstipasyon, obstipasyon ve abdominal distansiyon yaygın olarak görülür. Kontrastlı tomografik inceleme hastalığın tanısında kullanılan altın standart görüntüleme tekniğidir. Hastalığın tedavi algoritması konusunda tartışmalar mevcuttur. Genel olarak basit entorotomi, tek aşamalı cerrahi ve iki aşamalı cerrahiyi öneren çalışmalar mevcuttur. Cerrahi planlanmasında hastanın yaşı, komorbiditeleri, sıvı- elektrolit dengesi ve obstrüksiyon oluşan segment göz önünde bulundurulur. Biz de çalışmamızda Cerrahpaşa Tıp Fakültesi Acil Servisi’ne ileus semptomları ile başvurup yapılan tetkikler sonucunda safra taşı ileusu saptanan hastanın tanı ve tedavi algoritmasını sunuyoruz. Cite this article as: Tunç E, Şimşek S, Pekmezci S. A rare cause of ileus: Gallstone ileus. Cerrahpaşa Med J. 2022;46(1):80-82.